Utilizace glukózy a riziko hyperglykémie pri soucasném podávání vĕtvených aminokyselin a tukové emulze u zdravých osob - Pelikánová, T; Kohout, M; Válek, J; Karasová, L; Base, J; Stefka, Z (Casopis lekaru ceskych, 1993)
In order to evaluate the effect of substrate competition on glucose utilization, we studied 8 healthy volunteers under three different conditions: 1. Hyperinsulinemic (75 a 550 microU/ml) euglycemic (5 mmol/1) clamp (HEC). 2. HEC with Nutramin VLI infusion given at a rate of 2 ml/kg.h. 3. HEC with infusion of Nutramin VLI (2 ml/kg.h) and Intralipid (0.15 g of fat/kg.h). Glucose utilization was evaluated as the glucose disposal rate during HEC. We have found, that Nutramin VLI given alone or with Intralipid does not significantly decrease glucose utilization at insulinemia of about 75 and 550 microU/ml. We conclude that simultaneous administration of substrates during parenteral nutrition at standard rates does not raise the risk of hyperglycemia in healthy men.
Keywords: tukové emulze intravenózní; Amino Acids, Branched-Chain; Humans; rizikové faktory; dospělí; lidé; Fat Emulsions, Intravenous; Blood Glucose; Glucose Tolerance Test; hyperglykemie; Hyperglycemia; Adult; glukózový toleranční test; Male; krevní glukóza; Infusions, Intravenous; větvené aminokyseliny; mužské pohlaví; intravenózní infuze; Risk Factors